Method for preparing superfine nano silicon material by using clay mineral and application of superfine nano silicon material

By using thermal reduction reaction of clay minerals with metal reducing agents and high viscosity inorganic salts, high-purity, ultra-fine nano-silicon materials were prepared, which solved the silicon volume changes and electrolyte interface problems in lithium-ion batteries, and achieved low cost and easy scale The nano-silicon preparation produced by chemical production improves the cycle stability and lithium storage performance of the battery.

CN119263284APending Publication Date: 2025-01-07GUANGZHOU INSTITUTE OF GEOCHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411414798.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The volume change of the existing lithium-ion battery negative electrode material silicon during charging and discharge leads to mechanical fracture and damage to the electrolyte interface film, resulting in capacity attenuation and electrolyte consumption. The traditional method of preparing nano-silicon is high in cost, low yield, and is not suitable for industrial applications. .

Method used

Using clay minerals as raw materials, it is used to dehydrate at high temperature, mix with metal reducing agent and high viscosity inorganic salts, and undergo multiple thermal reduction reactions, and wash them with dilute acid and ultrapure water to prepare ultrafine fine grain size and high purity. Nanosilicon material.

Benefits of technology

It realizes the preparation of ultrafine nano-silicon with low cost and easy to produce on a large scale, improves the purity and yield of nano-silicon, reduces the preparation cost, is suitable for use in the negative electrode materials of lithium-ion batteries, improves the cycle stability and lithium storage of batteries performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263284A_ABST
    Figure CN119263284A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a superfine nano-silicon material by using clay minerals and application of the superfine nano-silicon material, and the method comprises the following steps: heating the clay minerals serving as raw materials to prepare dehydrated clay minerals; uniformly mixing the dehydrated clay minerals with a metal reducing agent and fused salt in proportion, and heating and preserving heat under protective gas; after cooling, continuously adding a metal reducing agent into the mixture, heating and preserving heat under the same condition, and repeating the process for multiple times; and washing the obtained mixture with dilute acid and ultrapure water, centrifuging and drying to obtain the superfine nano silicon material. The prepared nano silicon has the characteristics of small grain size, high purity, hierarchical pore structure and the like, and can be applied to a lithium ion battery negative electrode material. According to the method, the superfine nano silicon material can be prepared by changing a dehydration mode, molten salt characteristics and a reducing agent adding mode from the perspective of actual industrialization, the preparation cost of the nano silicon is effectively reduced, the preparation process is simple and controllable, the batch stability is high, and large-scale preparation is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of efficient utilization of mineral resources and lithium ion batteries, and specifically relates to a method for preparing ultrafine nano silicon materials by utilizing clay minerals and application thereof. Background Art

[0002] The rapid development of electric vehicles, mobile electronic devices, smart grids and many other devices has put forward higher requirements for the volume energy density and cycle life of lithium-ion batteries. Silicon is considered to be the most promising negative electrode material for lithium-ion batteries, and its theoretical specific capacity is far superior to commercial graphite negative electrode materials (4200vs 372mAh g -1 ), and its discharge potential is close to that of metallic lithium (~0.2V). However, the silicon negative electrode undergoes a huge volume change during the charge and discharge cycle, and the stress generated can cause the silicon particles to break and pulverize, and lose effective electrical contact with the current collector, resulting in rapid capacity decay; in addition, the continuous destruction and regeneration of the solid electrolyte interface film (SEI) leads to continuous consumption of electrolyte and increase in SEI film thickness, increasing Li +Diffusion and electronic conduction resistance. At present, researchers have proposed various modification strategies from the aspects of electrolyte, adhesive, silicon-carbon composite materials, etc. Among them, the preparation of nano-silicon is the key to the commercial application of silicon-based negative electrodes, because the nanostructure can effectively inhibit the mechanical fracture caused by severe volume changes during silicon lithiation / delithiation. The methods currently used to prepare nano-silicon mainly include ball milling, chemical vapor deposition, chemical reduction and other methods. The traditional mechanical ball milling method has the advantages of low cost, simple operation, and easy scalability, but the prepared nano-silicon has low purity and large particle size (>100nm), which is difficult to meet the needs of high-quality ultrafine nano-silicon negative electrodes. In contrast, the chemical vapor deposition method is easy to prepare nano-silicon with small particle size, high purity and excellent electrochemical performance, but the preparation method is costly, low in yield and low in safety, which hinders its industrial application. The metal thermal reduction method uses the strong reducing property of metals to reduce silicon in silicon oxide. Silicon in nature is mainly present in the form of silicon oxide and silicate and is widely present in the earth's crust. Compared with other preparation methods, metal thermal reduction has cost advantages. However, the metal thermal reduction method still has the following problems: (1) The metal thermal reduction method is a solid-phase diffusion reaction. If the silica precursor and the metal reducing agent are not mixed evenly, it is easy to cause problems such as incomplete reduction reaction and low yield. Most of the silicon oxides and silicates in the earth's crust exist in the form of stable, high-crystallinity minerals (such as quartz, olivine, feldspar, etc.), with large particle size and difficult to break. In addition, silicate minerals are hydrophilic and have high water content. Water is easy to cause side reactions with metal reducing agents, resulting in increased reducing agent dosage and low yield; (2) The actual reaction temperature inside the self-exothermic reaction is high, resulting in particle melting and crystallization growth, making it difficult to prepare small-sized nano-silicon particles; (3) The actual reaction temperature inside the exothermic reaction is uncontrollable, causing the material temperature to be too high to produce side reactions and introduce by-products, resulting in low product purity and poor batch stability, which is not suitable for large-scale industrial production. Therefore, it is crucial to develop a method for preparing ultrafine nano-silicon that can achieve scale and good cost-effectiveness. Summary of the invention

[0003] In view of this, in order to solve the above-mentioned technical problems, the purpose of the present invention is to provide a method for preparing ultrafine nano-silicon at low cost using clay minerals. The method is simple and easy, has high yield, low cost, and a green and controllable preparation process. It is easy to mass produce, providing a new method for low-cost and large-scale preparation of ultrafine nano-silicon.

[0004] Another object of the present invention is to provide an ultrafine nano-silicon material with small grain size, high purity and multi-level pore structure.

[0005] Another object of the present invention is to provide an application of ultrafine nano-silicon material in lithium-ion batteries.

[0006] In order to achieve the above technical objectives, the technical solutions adopted are as follows:

[0007] A method for preparing ultrafine nano-silicon materials using clay minerals, the method comprising the following schemes:

[0008] Scenario 1:

[0009] Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with metal reducing agent and inorganic salt in proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to carry out thermal reduction reaction; after cooling, continuing to add metal reducing agent to the obtained mixture, and then heating and keeping warm under the same conditions to carry out thermal reduction reaction, and repeating the process several times; washing the final mixture with dilute acid and ultrapure water, and centrifuging and drying to obtain ultrafine nano silicon material;

[0010] Scenario 2:

[0011] Using clay mineral as raw material, the clay mineral is uniformly mixed with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions used; heating and heat preservation are performed under protective gas to carry out a thermal reduction reaction; after cooling, the metal reducing agent is continuously added to the obtained mixture, and then heating and heat preservation are performed under the same conditions to carry out a thermal reduction reaction, and the process is repeated several times; the final obtained mixture is washed with dilute acid and ultrapure water, and centrifuged and dried to obtain an ultrafine nano-silicon material;

[0012] Scenario 3:

[0013] Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with metal reducing agent and inorganic salt in proportion, wherein the viscosity of the inorganic salt is less than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to carry out thermal reduction reaction; after cooling, continuing to add metal reducing agent to the obtained mixture, and then heating and keeping warm under the same conditions to carry out thermal reduction reaction, and repeating the process several times; washing the final mixture with dilute acid and ultrapure water, and centrifuging and drying to obtain ultrafine nano silicon material;

[0014] Solution 4:

[0015] Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to perform thermal reduction reaction; washing the final mixture with dilute acid and ultrapure water, centrifuging and drying to obtain ultrafine nano-silicon material;

[0016] Solution 5:

[0017] Using clay mineral as raw material, the clay mineral is uniformly mixed with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is less than 1 mPa.s under the temperature conditions used; heating and heat preservation are performed under protective gas for thermal reduction reaction; after cooling, the metal reducing agent is continuously added to the obtained mixture, and then heating and heat preservation are performed under the same conditions for thermal reduction reaction, and the process is repeated several times; the final obtained mixture is washed with dilute acid and ultrapure water, and centrifuged and dried to obtain an ultrafine nano-silicon material;

[0018] Solution 6:

[0019] Using clay mineral as raw material, the clay mineral is uniformly mixed with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions used; heating and heat preservation are performed under protective gas to perform a thermal reduction reaction; the final mixture is washed with dilute acid and ultrapure water, and centrifuged and dried to obtain an ultrafine nano-silicon material;

[0020] Solution 7:

[0021] Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is less than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to perform thermal reduction reaction; washing the final mixture with dilute acid and ultrapure water, centrifuging and drying to obtain ultrafine nano-silicon material;

[0022] Furthermore, the clay mineral is a natural clay mineral and a modified clay mineral; the natural clay mineral is at least one of montmorillonite, kaolinite, halloysite, vermiculite, pyrophyllite, chlorite, talc, palygorskite, sepiolite, black talc, serpentine, biotite, muscovite, illite, and saponite; the modified clay mineral is a clay mineral product obtained by modifying a natural clay mineral through physical and chemical reactions.

[0023] Furthermore, the physical and chemical modification method includes one or more of sand milling, ball milling, ultrasonic stripping, acid etching, and alkaline etching.

[0024] Furthermore, the dehydrated clay mineral is a product obtained by calcining a natural clay mineral or a modified clay mineral at a high temperature of 400 to 1000°C.

[0025] The dehydration methods include a slow heating method and a fast heating method. The heating rate of the slow heating method does not exceed 1°C / s, the insulation time is 0.1 to 24h, and the insulation temperature is 400 to 700°C; the heating rate of the fast heating method is 1 to 10000°C / s, the insulation temperature is 700 to 1000°C, and the insulation time is less than 0.5h.

[0026] Natural clay minerals are a class of finely dispersed (<2μm), hydrated layered silicate minerals, layered chain silicate minerals and hydrated amorphous silicate minerals. The mass proportion of adsorbed water, interlayer water and structural water in natural clay minerals is about 5% to 25%. Water will react with metal reducing agents, increase or decrease the amount of metal reducing agents, and reduce the reaction yield. Therefore, before metal thermal reduction, it is crucial to remove the adsorbed water, interlayer water and structural water in clay minerals at high temperature to improve the yield; moreover, when a rapid removal method is used, the interlayer water of clay minerals is vaporized in a short time, thereby peeling off the clay mineral sheets, effectively increasing the specific surface area, which is conducive to the subsequent contact reaction with magnesium atoms. In addition, due to the natural micro-nano size, porous structure, and large specific surface area of ​​clay minerals, compared with other silicate minerals (feldspar, tourmaline, amphibole, etc.), clay minerals are easy to mix evenly with metal powders, making the thermal reduction reaction uniform and thorough. Therefore, clay minerals are ideal raw materials for the preparation of nano-silicon materials by metal thermal reduction of silicon oxides. Furthermore, physical crushing or chemical etching of clay minerals can reduce the particle size of clay minerals, increase the specific surface area of ​​clay minerals and the silicon content in the precursor, which can not only improve the yield but also reduce the grain size of nano-silicon.

[0027] Furthermore, the mass ratio of the dehydrated clay mineral, the metal reducing agent and the inorganic salt is 1:0.5-3:0.1-10; the metal reducing agent is at least one of metal magnesium, metal sodium, metal aluminum and metal zinc; and the inorganic salt is one or more of alkali metal and alkaline earth metal salts.

[0028] Further, the inorganic salt is at least one of sodium chloride, potassium chloride, lithium chloride, magnesium chloride, calcium chloride, sodium nitrate, potassium nitrate, and lithium nitrate. Preferably, the inorganic salt is at least one of magnesium chloride, calcium chloride, sodium nitrate, potassium nitrate, and lithium nitrate.

[0029] The role of the metal reducing agent is to reduce the silicon oxide in the mineral by using its strong reducing property. On the one hand, the inorganic salt acts as a heat absorber, absorbing a large amount of heat released during the metal thermal reduction process, making the temperature of the reaction system controllable, preventing the formation of impurities, and facilitating stable batch production; on the other hand, the high-viscosity inorganic salt acts as a barrier to effectively prevent the melting and aggregation of nano-silicon particles to form ultra-fine nano-silicon.

[0030] Furthermore, the reaction temperature is 500-900°C; the reaction time is 0.5-20h; the thermal reduction reaction is repeated at least twice; the protective gas is at least one of the rare gases; the pickling is dilute acid washing, and the dilute acid includes one or more of hydrochloric acid, sulfuric acid, nitric acid or phosphoric acid, and the concentration of the dilute acid used is 5-20wt%; the washing time is 1-24h.

[0031] Furthermore, after the acid washing, the substrate is immersed in a dilute hydrofluoric acid solution for 2 to 30 minutes, then washed with ultrapure water until neutral and dried; the concentration of the hydrofluoric acid is 0.1 to 10 wt%.

[0032] The present invention provides a porous silicon nanomaterial with small grain size and high purity, which is prepared by adopting any of the preparation methods described above.

[0033] In a third aspect, the present invention provides the use of the aforementioned nano-silicon material in a lithium electronic battery.

[0034] The beneficial effects of the present invention are embodied in:

[0035] The present invention uses high temperature to remove the adsorbed water, interlayer water and structural water in the clay mineral before metal thermal reduction, which is crucial to improving the yield; when a rapid loss method is adopted, the interlayer water of the clay mineral is gasified in a short time, thereby peeling off the clay mineral layer, effectively increasing the specific surface area, and facilitating the subsequent contact reaction with magnesium atoms. Then, dehydrated clay minerals are used as raw materials, and the nanostructure and silicon-rich properties of clay minerals are fully utilized, effectively avoiding the use of high-cost artificially synthesized silicon dioxide nanospheres, reducing the cost of raw materials. Secondly, dehydrated clay minerals contain almost no adsorbed water and structural water, effectively avoiding the reaction of metal reducing agents with water, effectively reducing the amount of reducing agents, and improving the yield. For example, the water content of 1g of natural montmorillonite is about 13%. Relative to 1g of dehydrated clay minerals, under the same conditions, the theoretical amount of additional magnesium powder reducing agent required for metal thermal reduction of natural montmorillonite is 0.173g. The theoretical nano-silicon yield of 1g natural montmorillonite is 0.271g, while the theoretical nano-silicon yield of 1g dehydrated montmorillonite is 0.312g. In addition, the product size of metal thermal reduction is closely related to the size of the silica precursor. The smaller the size of the clay mineral, the easier it is to produce nano-silicon particles with small particle size. On the other hand, the high-viscosity inorganic salt can not only absorb the heat released by the system during the metal thermal reduction process, making the system reaction temperature controllable, inhibiting the formation of high-temperature phases, and forming high-purity nano-silicon; the high-viscosity inorganic salt can also act as an isolation barrier to hinder the melting growth of silicon grains and form ultra-fine nano-silicon. Finally, the present invention proposes to add a metal reducing agent in multiple steps, which can effectively control the reaction process, prevent the rapid accumulation of heat and the rapid rise of the system temperature, and avoid the melting and growth of newly generated nano-silicon crystals. From the perspective of practicality, this method can realize the preparation of ultra-fine nano-silicon materials by changing the dehydration method, the characteristics of the molten salt, and the method of adding the reducing agent, effectively reducing the cost of nano-silicon preparation, and the preparation process is simple and controllable, with high batch stability and easy large-scale preparation.

[0036] The nano silicon prepared by the method of the present invention has the characteristics of high purity, small grain size (less than 50nm) and multi-level pore structure, and can be applied to the field of negative electrode materials for lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 is the X-ray diffraction pattern of the product prepared in Example 1 of the present invention;

[0039] Figure 2 is a transmission electron microscope image of the product prepared in Example 1 of the present invention;

[0040] Figure 3 This is a cycle performance diagram of the product prepared in Example 1 of the present invention used as a negative electrode material for a lithium-ion battery. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0042] A method for preparing ultrafine nano-silicon materials using clay minerals, the method comprising the following schemes:

[0043] Scenario 1:

[0044] Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with metal reducing agent and inorganic salt in proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to carry out thermal reduction reaction; after cooling, continuing to add metal reducing agent to the obtained mixture, and then heating and keeping warm under the same conditions to carry out thermal reduction reaction, and repeating the process several times; washing the final mixture with dilute acid and ultrapure water, and centrifuging and drying to obtain ultrafine nano silicon material;

[0045] Scenario 2:

[0046] Using clay mineral as raw material, the clay mineral is uniformly mixed with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions used; heating and heat preservation are performed under protective gas to carry out a thermal reduction reaction; after cooling, the metal reducing agent is continuously added to the obtained mixture, and then heating and heat preservation are performed under the same conditions to carry out a thermal reduction reaction, and the process is repeated several times; the final obtained mixture is washed with dilute acid and ultrapure water, and centrifuged and dried to obtain an ultrafine nano-silicon material;

[0047] Scenario 3:

[0048] Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with metal reducing agent and inorganic salt in proportion, wherein the viscosity of the inorganic salt is less than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to carry out thermal reduction reaction; after cooling, continuing to add metal reducing agent to the obtained mixture, and then heating and keeping warm under the same conditions to carry out thermal reduction reaction, and repeating the process several times; washing the final mixture with dilute acid and ultrapure water, and centrifuging and drying to obtain ultrafine nano silicon material;

[0049] Solution 4:

[0050] Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to perform thermal reduction reaction; washing the final mixture with dilute acid and ultrapure water, centrifuging and drying to obtain ultrafine nano-silicon material;

[0051] Solution 5:

[0052] Using clay mineral as raw material, the clay mineral is uniformly mixed with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is less than 1 mPa.s under the temperature conditions used; heating and heat preservation are performed under protective gas for thermal reduction reaction; after cooling, the metal reducing agent is continuously added to the obtained mixture, and then heating and heat preservation are performed under the same conditions for thermal reduction reaction, and the process is repeated several times; the final obtained mixture is washed with dilute acid and ultrapure water, and centrifuged and dried to obtain an ultrafine nano-silicon material;

[0053] Solution 6:

[0054] Using clay mineral as raw material, the clay mineral is uniformly mixed with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions used; heating and heat preservation are performed under protective gas to perform a thermal reduction reaction; the final mixture is washed with dilute acid and ultrapure water, and centrifuged and dried to obtain an ultrafine nano-silicon material;

[0055] Solution 7:

[0056] Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is less than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to perform thermal reduction reaction; washing the final mixture with dilute acid and ultrapure water, centrifuging and drying to obtain ultrafine nano-silicon material;

[0057] Furthermore, the clay mineral is a natural clay mineral and a modified clay mineral; the natural clay mineral is at least one of montmorillonite, kaolinite, halloysite, vermiculite, pyrophyllite, chlorite, talc, palygorskite, sepiolite, black talc, serpentine, biotite, muscovite, illite, and saponite; the modified clay mineral is a clay mineral product obtained by modifying a natural clay mineral through physical and chemical reactions.

[0058] Furthermore, the physical and chemical modification method includes one or more of sand milling, ball milling, ultrasonic stripping, acid etching, and alkaline etching.

[0059] Furthermore, the dehydrated clay mineral is a product obtained by calcining a natural clay mineral or a modified clay mineral at a high temperature of 400 to 1000°C.

[0060] The dehydration methods include a slow heating method and a fast heating method. The heating rate of the slow heating method does not exceed 1°C / s, the insulation time is 0.1 to 24h, and the insulation temperature is 400 to 700°C; the heating rate of the fast heating method is 1 to 10000°C / s, the insulation temperature is 700 to 1000°C, and the insulation time is less than 0.5h.

[0061] Natural clay minerals are a class of finely dispersed (<2μm), hydrated layered silicate minerals, layered chain silicate minerals and hydrated amorphous silicate minerals. The mass proportion of adsorbed water, interlayer water and structural water in natural clay minerals is about 5% to 25%. Water will react with metal reducing agents, increase or decrease the amount of metal reducing agents, and reduce the reaction yield. Therefore, before metal thermal reduction, it is crucial to remove the adsorbed water, interlayer water and structural water in clay minerals at high temperature to improve the yield; moreover, when a rapid removal method is used, the interlayer water of clay minerals is vaporized in a short time, thereby peeling off the clay mineral sheets, effectively increasing the specific surface area, which is conducive to the subsequent contact reaction with magnesium atoms. In addition, due to the natural micro-nano size, porous structure, and large specific surface area of ​​clay minerals, compared with other silicate minerals (feldspar, tourmaline, amphibole, etc.), clay minerals are easy to mix evenly with metal powders, making the thermal reduction reaction uniform and thorough. Therefore, clay minerals are ideal raw materials for the preparation of nano-silicon materials by metal thermal reduction of silicon oxides. Furthermore, physical crushing or chemical etching of clay minerals can reduce the particle size of clay minerals, increase the specific surface area of ​​clay minerals and the silicon content in the precursor, which can not only improve the yield but also reduce the grain size of nano-silicon.

[0062] Furthermore, the mass ratio of the dehydrated clay mineral, the metal reducing agent and the inorganic salt is 1:0.5-3:0.1-10; the metal reducing agent is at least one of metal magnesium, metal sodium, metal aluminum and metal zinc; and the inorganic salt is one or more of alkali metal and alkaline earth metal salts.

[0063] Further, the inorganic salt is at least one of sodium chloride, potassium chloride, lithium chloride, magnesium chloride, calcium chloride, sodium nitrate, potassium nitrate, and lithium nitrate. Preferably, the inorganic salt is at least one of magnesium chloride, calcium chloride, sodium nitrate, potassium nitrate, and lithium nitrate.

[0064] The inorganic salt is an inorganic salt with a viscosity greater than 1 mPa.s under the conditions near the temperature used, such as at least one of sodium chloride, potassium chloride, lithium chloride, magnesium chloride, calcium chloride, sodium nitrate, potassium nitrate, and lithium nitrate; more preferably, the inorganic salt is an inorganic salt with a viscosity greater than 2 mPa.s, such as at least one of magnesium chloride, calcium chloride, sodium nitrate, potassium nitrate, and lithium nitrate. As an endothermic agent, the inorganic salt effectively absorbs the excess heat released during the thermal reduction process, prevents the generation of high-temperature impurities due to excessive temperature, and is easy to prepare high-purity ultrafine nano-silicon; the high-viscosity inorganic salt can also effectively prevent the melting and aggregation of nano-silicon particles after melting, which is conducive to the formation of ultrafine nano-silicon crystals. It is worth noting that the viscosity of the inorganic salt will decrease as the temperature used increases, so the reduction reaction temperature used should not be too high.

[0065] The role of the metal reducing agent is to reduce the silicon oxide in the mineral by using its strong reducing property. On the one hand, the inorganic salt acts as a heat absorber, absorbing a large amount of heat released during the metal thermal reduction process, making the temperature of the reaction system controllable, preventing the formation of impurities, and facilitating stable batch production; on the other hand, the high-viscosity inorganic salt acts as a barrier to effectively prevent the melting and aggregation of nano-silicon particles to form ultra-fine nano-silicon.

[0066] Furthermore, the reaction temperature is 500-900°C; the reaction time is 0.5-20h; the thermal reduction reaction is repeated at least twice; the protective gas is at least one of the rare gases; the pickling is dilute acid washing, and the dilute acid includes one or more of hydrochloric acid, sulfuric acid, nitric acid or phosphoric acid, and the concentration of the dilute acid used is 5-20wt%; the washing time is 1-24h.

[0067] Furthermore, after the acid washing, the substrate is immersed in a dilute hydrofluoric acid solution for 2 to 30 minutes, then washed with ultrapure water until neutral and dried; the concentration of the hydrofluoric acid is 0.1 to 10 wt%.

[0068] The inventors found that the best product quality was obtained after the mixture was washed with dilute acid and then soaked in dilute hydrofluoric acid solution. The reason is that after soaking in dilute hydrofluoric acid solution, the silicon oxide compounds on the silicon surface and / or the SiO2 that has not been completely reacted can be removed. 2 , further reducing impurities.

[0069] An embodiment of the present invention also provides a product prepared by the above method.

[0070] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0071] Embodiment 1:

[0072] A method for preparing ultrafine nano-silicon using clay minerals comprises the following steps:

[0073] 10g of natural montmorillonite was added to 1L of 10wt% sulfuric acid solution for reaction for 12h, centrifuged, washed with ultrapure water until neutral, dried at 60℃ for 5h to obtain acid-etched montmorillonite, and then placed in a high-temperature furnace, heated to 500℃ at 10℃ / min, and kept warm for 5h to obtain dehydrated montmorillonite. Then 1g of dehydrated montmorillonite, 0.42g of metal magnesium powder and 5g of calcium chloride were mixed evenly, and then placed in a tubular furnace, calcined at 650℃ for 2h under argon atmosphere (the viscosity of calcium chloride at this temperature is greater than 1mPa.s); after cooling, 0.42g of metal magnesium powder was continued to be added to the obtained mixture, and then kept warm at 650℃ for 3h under argon atmosphere. After natural cooling, the obtained mixture was first washed with 3wt% dilute hydrochloric acid solution for 5h, then soaked with 1wt% dilute hydrofluoric acid solution for 5min, washed with ultrapure water until neutral, filtered and dried to obtain the final product ultrafine nano silicon.

[0074] The results show that the obtained material has characteristic diffraction peaks at 28.4, 47.3, 56.1, 69.1, and 76.3° (2θ), which belong to the characteristic diffraction peaks of crystalline silicon, and no diffraction peaks of other impurity phases appear, such as Figure 1 As shown in Figure 2, the crystallite size calculated by Scherrer's formula is 15 nm. Transmission electron microscopy data show that the product is in irregular granular form, forming agglomerates with micropores and mesopores; Figure 2 As shown in the figure, the energy spectrum analysis results show that the mass proportions of silicon and oxygen in the sample are 91% and 8% respectively. A small amount of oxygen may come from the surface oxidation of silicon particles, indicating that the sample is of high purity. The specific surface area of ​​the sample is about 86m 2 g -1 The total pore volume is about 0.30 cm 3 g -1 The total mass of the obtained product was 0.35 g, and the calculated yield was 34%.

[0075] Embodiment 2:

[0076] A method for preparing ultrafine nano-silicon using clay minerals comprises the following steps:

[0077] 10g of natural montmorillonite was added to 1L of 10wt% sulfuric acid solution for 12h, centrifuged, washed with ultrapure water until neutral, and dried at 60℃ for 5h to obtain acid-etched montmorillonite. Then 1g of acid-etched montmorillonite, 0.42g of magnesium powder and 5g of calcium chloride were mixed evenly, and then placed in a tube furnace and calcined at 650℃ for 2h under argon atmosphere (the viscosity of calcium chloride at this temperature is greater than 1mPa.s); after cooling, 0.42g of magnesium powder was added to the obtained mixture, and then kept at 650℃ for 3h under argon atmosphere. After natural cooling, the obtained mixture was first washed with 3wt% dilute hydrochloric acid solution for 5h, then soaked in 1wt% dilute hydrofluoric acid solution for 5min, washed with ultrapure water until neutral, filtered and dried to obtain the final product, ultrafine nano silicon. The grain size of the obtained ultrafine nano silicon is 21nm, and the yield is 27%.

[0078] Embodiment 3:

[0079] A method for preparing ultrafine nano-silicon using clay minerals comprises the following steps:

[0080] 10g of natural montmorillonite was added to 1L of 10wt% sulfuric acid solution for reaction for 12h, centrifuged, washed with ultrapure water until neutral, dried at 60℃ for 5h to obtain acid-etched montmorillonite, and then placed in a high-temperature furnace, heated to 500℃ at 10℃ / min, and kept warm for 5h to obtain dehydrated montmorillonite. Then 1g of dehydrated montmorillonite, 0.42g of metal magnesium powder and 5g of potassium chloride were mixed evenly, and then placed in a tube furnace, calcined at 850℃ for 2h under argon atmosphere (the viscosity of potassium chloride at this temperature is ~0.9mPa.s); after cooling, 0.42g of metal magnesium powder was added to the obtained mixture, and then kept warm at 850℃ for 3h under argon atmosphere. After natural cooling, the obtained mixture was first washed with 3wt% dilute hydrochloric acid solution for 5h, then soaked with 1wt% dilute hydrofluoric acid solution for 5min, washed with ultrapure water until neutral, filtered and dried to obtain the final product ultrafine nano silicon. The grain size of the obtained ultrafine nano-silicon is 38 nm, and the yield is 30%.

[0081] Embodiment 4:

[0082] A method for preparing ultrafine nano-silicon using clay minerals comprises the following steps:

[0083] 10g natural montmorillonite was added to 1L 10wt% sulfuric acid solution for 12h, centrifuged, washed with ultrapure water until neutral, dried at 60℃ for 5h to obtain acid-etched montmorillonite, and then placed in a high-temperature furnace, heated to 500℃ at 10℃ / min, and kept warm for 5h to obtain dehydrated montmorillonite. Then 1g dehydrated montmorillonite, 0.84g metal magnesium powder and 5g calcium chloride were mixed evenly, and then placed in a tubular furnace and calcined at 650℃ for 5h under argon atmosphere (the viscosity of calcium chloride at this temperature is greater than 1mPa.s). After natural cooling, the obtained mixture was first washed with 3wt% dilute hydrochloric acid solution for 5h, then soaked with 1wt% dilute hydrofluoric acid solution for 5min, washed with ultrapure water until neutral, filtered and dried to obtain the final product ultrafine nano silicon. The grain size of the obtained ultrafine nano silicon is 35nm, and the yield is 35%.

[0084] Embodiment 5:

[0085] A method for preparing ultrafine nano-silicon using clay minerals comprises the following steps:

[0086] 10g natural montmorillonite was added to 1L 10wt% sulfuric acid solution for reaction for 12h, centrifuged, washed with ultrapure water until neutral, and dried at 60℃ for 5h to obtain acid-etched montmorillonite. Then 1g acid-etched montmorillonite, 0.42g metal magnesium powder and 5g potassium chloride were mixed evenly, and then placed in a tube furnace and calcined at 850℃ for 2h under argon atmosphere (the viscosity of potassium chloride at this temperature is ~0.9mPa.s); after cooling, 0.42g metal magnesium powder was added to the obtained mixture, and then kept at 850℃ for 3h under argon atmosphere. After natural cooling, the obtained mixture was first washed with 3wt% dilute hydrochloric acid solution for 5h, then soaked in 1wt% hydrofluoric acid dilute solution for 5min, washed with ultrapure water until neutral, filtered and dried to obtain the final product ultrafine nano silicon. The grain size of the obtained ultrafine nano silicon is 43nm, and the yield is 26%.

[0087] Embodiment 6:

[0088] A method for preparing ultrafine nano-silicon using clay minerals comprises the following steps:

[0089] 10g of natural montmorillonite was added to 1L of 10wt% sulfuric acid solution to react for 12h, centrifuged, washed with ultrapure water until neutral, and dried at 60℃ for 5h to obtain acid-etched montmorillonite. Then 1g of acid-etched montmorillonite, 0.84g of magnesium powder and 5g of calcium chloride were mixed evenly, and then placed in a tube furnace and calcined at 650℃ for 5h under argon atmosphere (the viscosity of calcium chloride at this temperature is greater than 1mPa.s). After natural cooling, the obtained mixture was first washed with 3wt% dilute hydrochloric acid solution for 5h, then soaked in 1wt% dilute hydrofluoric acid solution for 5min, washed with ultrapure water until neutral, filtered and dried to obtain the final product, ultrafine nano silicon. The grain size of the obtained ultrafine nano silicon is 42nm, and the yield is 25%.

[0090] Embodiment 7:

[0091] A method for preparing ultrafine nano-silicon using clay minerals comprises the following steps:

[0092] 10g natural montmorillonite was added to 1L 10wt% sulfuric acid solution for 12h, centrifuged, washed with ultrapure water until neutral, dried at 60℃ for 5h to obtain acid-etched montmorillonite, and then placed in a high-temperature furnace, heated to 500℃ at 10℃ / min, and kept warm for 5h to obtain dehydrated montmorillonite. Then 1g dehydrated montmorillonite, 0.84g metal magnesium powder and 5g potassium chloride were mixed evenly, and then placed in a tubular furnace and calcined at 850℃ for 5h under argon atmosphere (the viscosity of potassium chloride at this temperature is ~0.9mPa.s). After natural cooling, the obtained mixture was first washed with 3wt% dilute hydrochloric acid solution for 5h, then soaked with 1wt% dilute hydrofluoric acid solution for 5min, washed with ultrapure water until neutral, filtered and dried to obtain the final product ultrafine nano silicon. The grain size of the obtained ultrafine nano silicon is 45nm, and the yield is 31%.

[0093] Embodiment 8:

[0094] A method for preparing ultrafine nano-silicon using clay minerals comprises the following steps:

[0095] 2g of natural montmorillonite is placed in a high-temperature furnace, heated to 600℃ at 5℃ / min, and kept warm for 3h to obtain dehydrated montmorillonite. 1g of dehydrated montmorillonite, 0.35g of magnesium powder and 3g of sodium chloride are mixed evenly, placed in a tube furnace, and kept warm at 650℃ for 2h under argon atmosphere (the viscosity of sodium chloride at this temperature is greater than 1mPa.s); after cooling, 0.35g of magnesium powder is added to the mixture, and then kept warm at 650℃ for 3h under argon atmosphere. After natural cooling, the mixture is first washed with 6wt% dilute hydrochloric acid solution for 5h, then washed with 1wt% dilute hydrofluoric acid solution for 3min, washed with ultrapure water until neutral, filtered and dried, and the final product, ultrafine nano-silicon, is obtained. The grain size of the obtained ultrafine nano-silicon is 19nm, and the yield is 26%.

[0096] Embodiment 9:

[0097] A method for preparing ultrafine nano-silicon using clay minerals comprises the following steps:

[0098] 0.5g natural vermiculite is placed in a high-temperature furnace, heated to 900℃ at 5000℃ / s, and kept warm for 60s to obtain dehydrated vermiculite. 0.3g dehydrated vermiculite, 0.1g metal magnesium powder, 1g sodium chloride and 0.5g magnesium chloride are mixed evenly, placed in a tube furnace, and kept warm at 680℃ for 2h under argon atmosphere (the viscosity of the mixed molten salt of sodium chloride and magnesium chloride is greater than 1mPa.s at this temperature); after cooling, 0.1g metal magnesium powder is continued to be added to the obtained mixture, and then kept warm at 680℃ for 2h under argon atmosphere; after cooling, 0.1g metal magnesium powder is continued to be added to the obtained mixture, and then kept warm at 680℃ for 2h under argon atmosphere. After natural cooling, the obtained mixture is first washed with 5wt% dilute hydrochloric acid solution for 10h, then washed with 2wt% dilute hydrofluoric acid solution for 2min, washed with ultrapure water until neutral, filtered and dried, and the final product ultrafine nano silicon can be obtained. The grain size of the obtained ultrafine nano-silicon is 14 nm, and the yield is 24%.

[0099] Embodiment 10:

[0100] A method for preparing ultrafine nano-silicon using clay minerals comprises the following steps:

[0101] 10g natural black talc and 50g 10mm diameter corundum balls are loaded into a corundum ball mill, ball milled at 500rpm for 2h, then the ball-milled black talc is added to 0.5L 20wt% hydrochloric acid solution, acid etched for 1h, centrifuged, washed with ultrapure water until neutral, then dried at 60℃ for 3h to obtain modified black talc, and then heated to 700℃ at 10℃ / min, kept warm for 20h to obtain dehydrated black talc. 5g dehydrated black talc, 4g metal magnesium powder, and 16g lithium chloride are mixed evenly, placed in a tube furnace, and kept warm at 720℃ for 6h under argon atmosphere (the viscosity of lithium chloride is greater than 1mPa.s at this temperature). After natural cooling, the resulting mixture is first washed with 10wt% dilute hydrochloric acid solution for 2h, then washed with 5wt% dilute hydrofluoric acid solution for 1min, washed with ultrapure water until neutral, filtered and dried, and the final product ultrafine nano silicon is obtained. The grain size of the obtained ultrafine nano-silicon is 40 nm, and the yield is 38%.

[0102] Application Example 1:

[0103] The nano-silicon material obtained in implementation 1-10 was used as the negative electrode material of lithium-ion battery to assemble CR2032 button cell. The active material (the obtained nano-silicon material), acetylene black and sodium alginate were mixed evenly in a mass ratio of 7:1.5:1.5, coated on copper foil, dried at 80°C for 10h under vacuum conditions, and cut to be used as the working electrode. The metal lithium sheet was used as the counter electrode, Celgard2500 was used as the diaphragm, and the electrolyte was composed of 1mol / L LiPF 6 , 90wt% EC / DMC (v / v 1:1), 10wt% FEC. The battery assembly process was carried out in an argon glove box, and the water and oxygen contents were both less than 0.01ppm.

[0104] like Figure 3 As shown, the porous nano-silicon material prepared in Example 1 is -1 Cyclic performance diagram under current density (the first three cycles are at 0.2A g -1 The results showed that the nano-silicon anode exhibited excellent lithium storage performance (1A g -1 After 100 cycles at the current density, the charge capacity is 1700 mAh g -1 ) and cycle stability (1A g -1 The capacity retention rate is 85% after 100 cycles), which has broad application prospects in the field of lithium-ion batteries.

[0105] In summary, the method for preparing ultrafine nano-silicon from clay minerals provided by the present invention avoids the use of artificially synthesized high-cost nano-silicon dioxide precursors, effectively reduces the additional consumption of metal reducing agents by clay mineral adsorbed water and structural hydroxyl water, thereby reducing the production cost of nano-silicon and improving the yield. At the same time, ultrafine nano-silicon with a grain size of less than 50nm can be prepared by reducing the size of clay minerals, adding high-viscosity inorganic salts, adding metal reducing agents multiple times, etc. In the process of metal thermal reduction, inorganic salts absorb the heat released by the reduction process, reduce the reaction temperature of the system, avoid the formation of high-temperature impurity phases, and are conducive to the preparation of high-purity nano-silicon; high-viscosity inorganic salts can also act as an isolation barrier to inhibit the melt crystallization growth of nano-silicon particles and achieve grain size regulation of nano-silicon.

[0106] The above description is not intended to impose any form of limitation on the present invention. Although the present invention has been disclosed through the above embodiments, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing ultrafine nano-silicon materials using clay minerals, characterized in that: The method comprises the following scheme: Scenario 1: Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to perform thermal reduction reaction; After cooling, a metal reducing agent is continuously added to the obtained mixture, and then heated and kept warm under the same conditions for thermal reduction reaction, and the process is repeated several times; the final mixture is washed with dilute acid and ultrapure water, and centrifuged and dried to obtain an ultrafine nano-silicon material; Scenario 2: Using clay mineral as raw material, the clay mineral is uniformly mixed with a metal reducing agent and an inorganic salt in a certain proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions used; heating and heat preservation are performed under protective gas to perform a thermal reduction reaction; After cooling, a metal reducing agent is continuously added to the obtained mixture, and then heated and kept warm under the same conditions for thermal reduction reaction, and the process is repeated several times; the final mixture is washed with dilute acid and ultrapure water, and centrifuged and dried to obtain an ultrafine nano-silicon material; Solution 3: Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is less than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to perform thermal reduction reaction; After cooling, a metal reducing agent is continuously added to the obtained mixture, and then heated and kept warm under the same conditions for thermal reduction reaction, and the process is repeated several times; the final mixture is washed with dilute acid and ultrapure water, and centrifuged and dried to obtain an ultrafine nano-silicon material; Solution 4: Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to perform thermal reduction reaction; The resulting mixture is washed with dilute acid and ultrapure water, centrifuged, and dried to obtain ultrafine nano-silicon material; Solution 5: Using clay mineral as raw material, the clay mineral is uniformly mixed with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is less than 1 mPa.s under the temperature conditions used; heating and heat preservation are performed under protective gas to perform a thermal reduction reaction; After cooling, a metal reducing agent is continuously added to the obtained mixture, and then heated and kept warm under the same conditions for thermal reduction reaction, and the process is repeated several times; the final mixture is washed with dilute acid and ultrapure water, and centrifuged and dried to obtain an ultrafine nano-silicon material; Solution 6: Using clay mineral as raw material, the clay mineral is uniformly mixed with a metal reducing agent and an inorganic salt in a certain proportion, wherein the viscosity of the inorganic salt is greater than 1 mPa.s under the temperature conditions used; heating and heat preservation are performed under protective gas to perform a thermal reduction reaction; The resulting mixture is washed with dilute acid and ultrapure water, centrifuged, and dried to obtain ultrafine nano-silicon material; Solution 7: Using clay mineral as raw material, preparing dehydrated clay mineral by heating; then mixing the dehydrated clay mineral with a metal reducing agent and an inorganic salt in proportion, wherein the viscosity of the inorganic salt is less than 1 mPa.s under the temperature conditions; heating and keeping warm under protective gas to perform thermal reduction reaction; The final mixture is washed with dilute acid and ultrapure water, centrifuged and dried to obtain ultrafine nano-silicon material.

2. A method for preparing ultrafine nano-silicon materials using clay minerals as claimed in claim 1, characterized in that: The clay minerals are natural clay minerals and modified clay minerals; the natural clay minerals are at least one of montmorillonite, kaolinite, halloysite, vermiculite, pyrophyllite, chlorite, talc, palygorskite, sepiolite, black talc, serpentine, biotite, muscovite, illite and saponite; the modified clay minerals are clay mineral products obtained by modifying natural clay minerals through physical and chemical reactions.

3. A method for preparing ultrafine nano-silicon materials using clay minerals as claimed in claim 2, characterized in that: The physical and chemical modification methods include one or more of sand milling, ball milling, ultrasonic stripping, acid etching, and alkaline etching.

4. A method for preparing ultrafine nano-silicon materials using clay minerals as claimed in claim 1, characterized in that: The dehydrated clay mineral is a product obtained by calcining a natural clay mineral or a modified clay mineral at a high temperature of 400 to 1000°C. The dehydration methods include a slow heating method and a fast heating method. The heating rate of the slow heating method does not exceed 1°C / s, the insulation time is 0.1 to 24h, and the insulation temperature is 400 to 700°C; the heating rate of the fast heating method is 1 to 10000°C / s, the insulation temperature is 700 to 1000°C, and the insulation time is less than 0.5h.

5. A method for preparing ultrafine nano-silicon materials using clay minerals as claimed in claim 1, characterized in that: The mass ratio of the dehydrated clay mineral, the metal reducing agent and the inorganic salt is 1:0.5-3:0.1-10; the metal reducing agent is at least one of metal magnesium, metal sodium, metal aluminum and metal zinc; and the inorganic salt is one or more of alkali metal and alkaline earth metal salts.

6. A method for preparing ultrafine nano-silicon material using clay minerals as claimed in claim 1, characterized in that: The inorganic salt is at least one of sodium chloride, potassium chloride, lithium chloride, magnesium chloride, calcium chloride, sodium nitrate, potassium nitrate and lithium nitrate.

7. A method for preparing ultrafine nano-silicon material using clay minerals as claimed in claim 1, characterized in that: The reaction temperature is 500-900°C; the reaction time is 0.5-20h; the thermal reduction reaction is repeated at least twice; the protective gas is at least one of the rare gases; the pickling is dilute acid washing, the dilute acid includes one or more of hydrochloric acid, sulfuric acid, nitric acid or phosphoric acid, and the concentration of the dilute acid used is 5-20wt%; the washing time is 1-24h.

8. A method for preparing ultrafine nano-silicon material using clay minerals as claimed in claim 1, characterized in that: After the acid washing, the substrate is immersed in a dilute hydrofluoric acid solution for 2 to 30 minutes, then washed with ultrapure water until neutral and dried; the concentration of the hydrofluoric acid is 0.1 to 10 wt %.

9. An ultrafine nano-silicon material, characterized in that: The compound is prepared by any one of the preparation methods described in claims 1 to 8.

10. The ultrafine nano-silicon material as claimed in claim 9, characterized in that: The ultrafine nano silicon material is used in lithium ion batteries.

Citation Information

Patent Citations

  • Preparation method for silicon nano material and application

    CN105084365A

  • Method for preparing Si / C composite material by employing oil shale residue as raw material

    CN108448077A

  • Method for preparing nanometer silicon by low-temperature fused salt medium

    CN109081350A

  • Method for preparing silicon-carbon nano composite material by using clay minerals and application of silicon-carbon nano composite material

    CN118630176A

  • Production of pure silicon

    US2972521A